Facile synthesis of diverse hetero polyaromatic hydrocarbons (PAHs) via the styryl Diels–Alder reaction of conjugated diynes. Issue 16 (4th July 2022) - Wei, Jingwen; Liu, Mengjia; Ye, Xiaohan; Zhang, Shuyao; Sun, Elaine; Shan, Chuan; Wojtas, Lukasz; Shi, Xiaodong
Abstract : The intramolecular styryl Diels–Alder reaction with conjugated diynes under thermally stable triazole-gold (TA–Au) catalytic conditions and the sequential transformation through alkyne activation to access various PAHs with high efficiency was reported for the first time. Abstract : The styryl dehydro-Diels–Alder reaction with a conjugated diyne is reported. While typical alkyne–styrene condensation requires elevated temperatures (>160 °C), the application of a conjugated diyne allowed for effective transformation under milder conditions (80 °C). The thermally stable triazole–gold (TA–Au) catalyst further improved the reaction yields (up to 95%), producing the desired alkynyl–naphthalene in a single step with molecular oxygen as the oxidant. Sequential alkyne activation resulted in various polyaromatic hydrocarbons (PAHs) in excellent yields, highlighting the efficiency of this new strategy for the preparation of PAHs with good functional group tolerance and structural diversity.